DINAMIKA PEMERINTAHAN MODERN DI INDONESIA DAN TANTANGAN PENCEGAHAN PENYALAHGUNAAN WEWENANG DALAM PERSPEKTIF HUKUM ADMINISTRASI NEGARA - Gunawan Widjaja (ADMIN: Jurnal Administrasi Negara, 2026)
This article analyses the dynamics of modern Indonesian governance in the post-1998 reform era, characterised by decentralisation, good governance and digital transformation, yet facing serious challenges in preventing the abuse of power as regulated under Law No. 30 of 2014 on Government Administration. Three main forms of abuse of power—exceeding authority (exces de pouvoir), misappropriation of authority (detournement de pouvoir), and acting arbitrarily—are discussed through a normative literature review using a content analysis approach. Challenges such as the fragmentation of regulations under the Anti-Corruption Law, weak APIP capacity, and the poor CPI 2025 score are addressed through strategies to strengthen preventive oversight, civil service meritocracy, the digitalisation of SPBE, and legal harmonisation to achieve clean and accountable state governance based on AUPB.